The September 19, 2017 Mw 7.1 Puebla-Mexico City earthquake: Observed rockfall and landslide activity. Issue 130 (March 2020) - Montgomery, Jack; Candia, Gabriel; Lemnitzer, Anne; Martinez, Alejandro
Abstract: This note documents key observations of slope instability and rockfall activity made by the UNAM-GEER reconnaissance team after the Mw 7.1 Puebla-Mexico City earthquake of September 19, 2017. The investigated sites were located in Mexico City and the states of Morelos, Puebla and Mexico. Sites were studied using a combination of ground surveys, UAV imagery, and terrestrial LiDAR imaging. The field reconnaissance efforts were supplemented by analysis of pre- and post-event satellite images to define the boundary of the region affected by earthquake-induced landslides. Most slope failures occurred in remote areas or areas that had a prior history of instability. Overall, the consequences of slope instabilities caused by the 2017 Puebla-Mexico City earthquake were relatively minor compared with the reported structural damage. More than 360 deaths were attributed to this earthquake of which one death was attributed to landslide activities. The size of the area affected by landslides and the intensity of shaking in these areas was consistent with relationships developed in previous studies. The lack of major effects from earthquake-induced landslides is consistent with previous earthquakes in central and southern Mexico and stands in sharp contrast to many parts of Central America where earthquake-induced landslides pose a significant hazard. Highlights: The GEER UNAM team documented multiple instances of slope instability following the 2017 Puebla-Mexico City earthquake Many failures occurred in areas that had a prior history of slope instability. Effects from landslides were relatively minor compared with damage to the built environment from earthquake shaking.